Classroom climate and absenteeism: modeling English achievement mediated by engagement - Majumder, Palash; Beri, Nimisha; Biswas, Salil (Institute of Advanced Engineering and Science, 2025)
This study investigates the intricate relationships between positive classroom climate, student engagement, English as a second language (ESL) achievement, and absenteeism among 240 secondary school students in West Bengal, India. Addressing a significant research gap within the multilingual Indian ESL context, the study proposes and tests a novel multiple mediation structural model using structural equation modeling (SEM). Findings reveal that a positive classroom climate significantly predicts higher student engagement (β=.598, p<0.001) and ESL achievement (β=0.476, p<0.001). Crucially, both engagement (β=-0.250, p=0.002) and ESL achievement (β=-0.186, p=0.015) are negatively associated with absenteeism, with classroom climate exerting substantial indirect effects on attendance (total indirect effect β=-0.238, p<0.001). This research, aligned with sustainable development goal 4 (SDG 4): quality and inclusive education, provides empirical evidence for fostering supportive learning environments and engagement practices to simultaneously improve academic outcomes and reduce absenteeism, particularly for ESL learners in underserved contexts.